United States Equestrian Federation (2006)
The vision of the Federation is to provide leadership for equestrian sport in the United States of America, promoting the pursuit of excellence from the grass roots to the Olympic Games, based on a foundation of fair, safe competition and the welfare of its human and equine athletes, and embracing this vision, to be the best national equestrian federation in the world.